Employment and social developments in Europe 2015 (Luxembourg, 2016)
"Success in raising employment levels and living standards in Europe depends on effective support policies as well as positive macro-economic strategies. In this respect, this year’s Employment and Social Developments review addresses a range of issues. It starts by looking at the contribution of entrepreneurship and self-employment to job creation and growth and the need to tackle the difficulties faced by the self-employed and notably micro and small companies. It then looks at the role of labour legislation in supporting more and better jobs and the need to strike the right balance between flexibility and protection. It then moves on to look at the best actions to avoid unemployment turning into long-term unemployment and inactivity. More broadly, given technology change, globalisation and population ageing, which translates into a reduction in the working-age population, the EU needs to increase employment and increase productivity. Mobility and migration can play an important role here. In relation to this, Europe needs to improve skills and better match skills with evolving demands. It also needs to promote labour market participation of older workers and women. Social policies, including pension policies and family policies (for example, child care and long-term care), can support longer working lives and increase employment of women. Promoting social dialogue and the involvement of social partners in the development of employment and social policies may help the implementation and effectiveness of such policies. The review is available in printed and electronic format in English. All the graphs and tables can be downloaded both in gif and excel format by accessing the individual chapters. "